Barking up the same tree: a comparison of ethnomedicine and canine ethnoveterinary medicine among the Aguaruna - Jernigan Kevin A (BMC, 2009)
Abstract Background This work focuses on plant-based preparations that the Aguaruna Jivaro of Peru give to hunting dogs. Many plants are considered to improve dogs' sense of smell or stimulate them to hunt better, while others treat common illnesses that prevent dogs from hunting. This work places canine ethnoveterinary medicine within the larger context of Aguaruna ethnomedicine, by testing the following hypotheses: H1 -- Plants that the Aguaruna use to treat dogs will be the same plants that they use to treat people and H2 -- Plants that are used to treat both people and dogs will be used for the same illnesses in both cases. Methods Structured interviews with nine key informants were carried out in 2007, in Aguaruna communities in the Peruvian department of Amazonas. Informants provided freelists of plants given to dogs and explained the purpose, preparation and route of administration used. For each plant, informants also described any uses for treating people. Botanical voucher specimens were collected and additional informal observations were made, accompanying people on hunting trips. Results Out of 35 plant species given to dogs, 29 (83%) are also given to humans for some medicinal purpose, while five are used only for dogs. However, the same plant is used to treat the same illness in both humans and dogs in only 53% of the cases. Forty-three percent of plants used to treat a particular illness for both dogs and people are administered in the same manner for both. Conclusion Results suggest that Aguaruna canine ethnoveterinary medicine is, at least partly, an independent cognitive domain. Some of the difference in plant use between dogs and people can be explained by the fact that certain diseases mentioned only apply to dogs. Although reports of canine ethnoveterinary medicine are very sparse in the literature, Aguaruna practices show some similarities with a few trends reported for other Amazonian societies, particularly, in the prevalence of the nasal route of administration, the use of plant-based psychoactives and in the importance of ants and wasps, in some form, for training dogs.